„Próba nowej całości". Tadeusza Różewicza poetyka totalna - Kunz, Tomasz (Przestrzenie Teorii, 2007)
The article presents a brief outline of the most popular features of Tadeusz Różewicz's poetics, that question the main structural dominants and institutional indicators of literariness ooted in conventional modes and rules shaping a modern model of literature. It does so, however, only to suggest that Różewicz's critical dependence on modern literary conventions is supplemented with a strong, though utopian, "totalizing intention" aimed at creation of the one, perfect, all encompassing text. Somatic, organic relations between artist and his work, expressed through the impressive metaphors and images of insemination, foetal development, and birth makes the poet's works a symbolic representation of the phantasm of a dismembered body. This fragmented imago should be integrated in the "total form of the text" which stands for illusive, both specular and speculative, unity of the self. Unity that is most desired, but always unattainable.